1995
DOI: 10.1016/0014-5793(94)01337-z
|View full text |Cite
|
Sign up to set email alerts
|

The widely used anesthetic agent propofol can replace α‐tocopherol as an antioxidant

Abstract: The cell membrane is protected against lipid peroxidation through endogenous antioxidants such as the lipid soluble a-tocopherol. The anesthetic agent propofol (2,6-diisopropylphenol) has a chemical structure which is similar to ot-tocopherol, since it also contains a phenolic OH-group. The transient protection of GSH against lipid peroxidation in control liver microsomes is not observed in microsomes deficient in a-tocopherol. Introducing propofol (2 and 5 tiM) restored the protective effect of GSH. Similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 16 publications
5
70
2
1
Order By: Relevance
“…Previous studies indicated that the well-known anti-oxidant properties of propofol might be related to its chemical structure, which is similar to that of phenol-based scavengers such as tocopherols. 1,9,[42][43][44] Indeed, a-tocopherol is reported to have a strong anti-oxidizing effect. 42 Similarly, propofol's inhibitory effect on COX might be ascribable to its structural similarity to c-tocopherol.…”
Section: Lps Pretreatmentmentioning
confidence: 99%
“…Previous studies indicated that the well-known anti-oxidant properties of propofol might be related to its chemical structure, which is similar to that of phenol-based scavengers such as tocopherols. 1,9,[42][43][44] Indeed, a-tocopherol is reported to have a strong anti-oxidizing effect. 42 Similarly, propofol's inhibitory effect on COX might be ascribable to its structural similarity to c-tocopherol.…”
Section: Lps Pretreatmentmentioning
confidence: 99%
“…Propofol (2,6-diisopropylphenol) is a lipidsoluble anesthetic agent that has a chemical structure similar to that of phenol-based free radical scavengers such as vitamin E (Aarts et al, 1995;Kokita et al, 1998). It is commonly used as an intravenous anesthetic in cardiac surgery and has been shown to decrease postischemic myocardial dysfunction (Kokita and Hara, 1996), infarct size (Ebel et al, 1999), and histologic degeneration (Ko et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is one of the intravenous agents searched for its antioxidising effect. Chemical structure of propofol (2,6-diisoproyl phenol) mimics butilised hydroxy toluen (BHT) and endogenous antioxidising agent alpha-tocopherol (vitamin E) which are phenol containing free oxygen radical scavengers and contains a phenolic hydroxy group [13]. All these molecules form complexes with either the cellular membranes or its structural components resulting in a less reactive molecules and each single propofol molecule can scavenger two free oxygen radicals [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…And other similar models of I/R injury on neurons [19], leucocytes [4] and erythrocytes [20] prooved that propofol has a preventive effect against I/R injury. Aarts et al has reported that propofol has a preventive role in cases such as coronary artery transplantation surgery, sepsis and burns, which of all lead into a decreased ontioxidising defense mechanism [13]. Also in some recent studies propofol has been reported to be a free radical scavenger due to its antioxidising property at anesthetic doses [21][22][23].…”
Section: Discussionmentioning
confidence: 99%